Pedigree breeding in early segregating generations of cowpea (Vigna unguiculata (L.) Walp) - Sunil R (Department of Plant Breeding and Genetics, College of Horticulture, 2017)
Pulses represent an essential component of agricultural food crops and considered as an important crop to meet food and nutritional security. They complement cereal crops in terms of dietary requirement as a source of protein and minerals. In several countries of the tropics and sub-tropics, cowpea serves as an important food legume. It plays an essential role in enrichment of daily diet, mainly as a grain and green pods. In general, cowpea seeds contain 23.4 per cent protein, 60.3 per cent carbohydrates and 1.8 per cent fat. It also provides considerable amount of vitamins and phosphorus. The protein availability in cowpea seeds and green pods is almost double/ triple the amount of available cereal protein. The average grain yield of cowpea is still low and no single variety is adaptable for all growing conditions. Exploiting genetic variability is an essential method, to overcome the complex nature of cowpea breeding and to identify an elite high yielding genotype. Selection of best lines with high yield and other associated characters, in segregating generations paves a way to develop new varieties. The present study aimed to evaluate the F2 and F3 generations for high yield and protein content in two crosses (H 10 and H 11), involving Anaswara, PKB 3 and PKB 4 as parents. In general, the F2 families of both the crosses showed high mean performance and variance over the parents. Grain yield showed very low phenotypic coefficient variation (PCV) and genotypic coefficient variation (GCV). All other characters showed a moderate PCV and GCV values in segregating generation expect for days to first flowering, days to first harvest and days to last harvest. Most of the characters showed high heritability (h2) in F2 generation. In F2, the lowest value for h2 was observed for single pod weight in H 10 family and for grain yield in H 11 family. Similarly, High genetic advance over mean (GAM) was exhibited by 100-seed weight in H 10 family and number of pods per plant in H 11 family. Selection based on characters with high h2 and high GAM will be highly effective.